Knowledge audit for References and Customer Services Unit at UNITEN library - Al-Omari Z.H.; Ahmad M.S. (2023)
Knowledge management has become a common phrase in many service-oriented or business-oriented and government or privately owned organizations. Consequently, libraries have followed suit in deploying knowledge management for the many benefits being realized by these organizations. In this paper, we consider the appropriateness of a mixed-method approach, which include both quantitative and qualitative techniques of collecting data to reinforce the fact that library reference and customer service trends are changing. The paper proves and acknowledges that knowledge audit is an approach for assessing the viability of knowledge sources for reference librarians in academic institutions. Our subject for this study is the Reference and Customer Services Unit (RSCU) of Universiti Tenaga Nasional (UNITEN). A knowledge map for the unit is conceived to show the locations of knowledge within the unit. 2011 IEEE.